1786 Mass. Acts 87 - (:unkn) unknown (My University, 1786)
Ch. 38: Prohibited being armed with clubs or other weapons while in a group of twelve or more and "unlawfully, routously, riotously, or tumutluously assembled."
Keywords: CARRY - INTENT TO COMMIT CRIME